2010
DOI: 10.1007/s00464-009-0819-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic subtotal colectomy for medically refractory ulcerative colitis: the time has come

Abstract: Laparoscopic STC confers the benefits of improved cosmesis, reduced intraoperative blood loss, negligible wound complications, and shorter hospital stay. Laparoscopy is a feasible and safe alternative to open STC in patients with UC refractory to medical therapy requiring urgent or emergent operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 23 publications
5
65
2
5
Order By: Relevance
“…Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010). These retrospective trials indicated that minimally invasive subtotal colectomy for selected patients with severe ulcerative colitis associated with a marked reduction in wound complication rate, time to return of bowel function, and mean hospital stay, although most of these studies have reported that the mean operating time was longer than open surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010). These retrospective trials indicated that minimally invasive subtotal colectomy for selected patients with severe ulcerative colitis associated with a marked reduction in wound complication rate, time to return of bowel function, and mean hospital stay, although most of these studies have reported that the mean operating time was longer than open surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have demonstrated the feasibility of laparoscopic emergency colectomy with a trend to shorter hospital stay, lower morbidity and less blood loss [10][11][12]. Even single-port laparoscopic colectomy with an end ileostomy at the site of the single port has been safely performed [13].…”
Section: Surgery For Acute Colitismentioning
confidence: 98%
“…Koh és mtsai a CU miatti urgens laparoszkópos műtétek vizsgálata alapján azt biztonságosnak találták, ileus és sebfertőzés terén jobb eredményeket írtak le a nyitott műtétekhez képest [22]. Két amerikai tanulmány hasonlóan kedvező eredményeket közölt ápolási idő, vér igény, kozmetikai eredmény, sebfertőzés terén sürgő-séggel végzett laparoszkópos szubtotális colectomiák kapcsán [23,24]. Egy nagy nemzetközi adatbázis adatai alapján a minimálisan invazív betegcsoport kedvezőbb eredményekkel bír morbiditás és mortalitás szempontjá-ból [6].…”
Section: Eredeti Közleményunclassified